2017
DOI: 10.1093/asj/sjw284
|View full text |Cite
|
Sign up to set email alerts
|

AbobotulinumtoxinA: A 25-Year History

Abstract: During the late 1960s and early 1970s, Alan Scott showed that intramuscular injections of botulinum toxin (BoNT) corrected nonaccommodative strabismus without resorting to surgery. The UK doctors who trained with Scott soon realized the significant potential offered by BoNT type A as a therapeutic option for several difficult-to-treat diseases. This led to a collaboration between these pioneering clinicians and the Centre for Applied Microbiology and Research at Porton Down, United Kingdom, and, in turn, to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 66 publications
0
38
0
Order By: Relevance
“…To this end, we created a rat model of paravertebral muscle atrophy by locally injecting BTX a zinc‐dependent endopeptidase neurotoxin that specifically targets the neuromuscular junction . Previous studies have shown that focal intramuscular injection of BTX effectively denervates muscles by inhibiting the release of acetylcholine at the neuromuscular junction, resulting in local paresis and atrophy of the targeted muscle . Thus, BTX is used clinically to manage skeletal muscle spasticity associated with cerebral palsy, as well as other neuromuscular diseases .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we created a rat model of paravertebral muscle atrophy by locally injecting BTX a zinc‐dependent endopeptidase neurotoxin that specifically targets the neuromuscular junction . Previous studies have shown that focal intramuscular injection of BTX effectively denervates muscles by inhibiting the release of acetylcholine at the neuromuscular junction, resulting in local paresis and atrophy of the targeted muscle . Thus, BTX is used clinically to manage skeletal muscle spasticity associated with cerebral palsy, as well as other neuromuscular diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that focal intramuscular injection of BTX effectively denervates muscles by inhibiting the release of acetylcholine at the neuromuscular junction, resulting in local paresis and atrophy of the targeted muscle . Thus, BTX is used clinically to manage skeletal muscle spasticity associated with cerebral palsy, as well as other neuromuscular diseases . It attenuates the forceful contractions generated by patients with cerebral palsy, thus decreasing the strength of the spastic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Botulinum Neurotoxin Type A (BoNT/A) is a 150 kDa metalloenzyme belonging to the family of neurotoxins produced by Clostridium botulinum which causes temporary muscle paralysis by inhibiting acetylcholine release at the neuromuscular junction [1-4]. The neuronal specificity and high potency of BoNT/A has allowed its use in the treatment of a large number of medical and aesthetic conditions [3, 5-7], relying on injection of picomolar (pM) concentrations of the toxin. Though BoNT/A has been the subject of extensive study, greater understanding of the complex mechanism associated with BoNT/A’s neuronal specificity and cellular entry could lead to further therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…8 The paper begins with the reports of outbreaks of botulism from back in the late 1700s and continues to the first publications describing botulism in the 1800s, then focusing on the 25-years since Dysport was launched in the United Kingdom. Examining the 25-year history of ABO provides us with a clearer picture of where the product came from and opens up novel lines of inquiry for future use.…”
mentioning
confidence: 99%